Análisis e la calidad del agua presente en el Parque Ecológico Distrital de Humedal Jaboque en los meses de septiembre y octubre del 2022 (2023)
The processes of urban densification have generated great changes in the formation of diverse ecosystems, in the case of the city of Bogotá, the strong urbanization that the city presented caused that wetland ecosystems were adjacent to neighborhoods of invasion, in the case of the Ecological Park Jaboque Wetland District (PEDH), which is one of the 15 official wetlands that are immersed in the urban matrix of the city of Bogotá, has presented a large number of environmental stressors that affect the physicochemical characteristics of the water, thus affecting the quality of the wetland water resource. The present study seeks to evaluate the quality of the water present in the Jaboque wetland district Ecological Park in the months of September and October 2022 and analyze the changes it has suffered in terms of water quality in comparison to similar works that have been carried out. In previous years, the physicochemical conditions of the wetland water quality were determined with data provided by the wetland group of the District Environment Secretariat.